So-called idiopathic scoliosis – disfiguring deformity in children, pain problems in adults. Information about biomechanical etiology, classification and therapy - Karski, Tomasz (Journal of Advanced Pediatrics and Child Health, 2020)
In the article presented the etiology of the so-called idiopathic scoliosis (Adolescent Idiopathic Scoliosis [AIS]), new classification, there are given rules of therapy and causal prophylaxis. This knowledge is based on observations from 1984, but essentially from the years 1995 – 2007. In 2001 it was given the first description in classification – “S” scoliosis in 1st group / type and “C” and “S” scoliosis in 2nd A / B group and types, in 2004 “I” scoliosis in 3rd group / type.